2016
DOI: 10.3892/ol.2016.4688
|View full text |Cite|
|
Sign up to set email alerts
|

PREX2 promotes the proliferation, invasion and migration of pancreatic cancer cells by modulating the PI3K signaling pathway

Abstract: Abstract. Phosphatidylinositol-3,4,5-trisphosphate-dependent Rac exchanger factor 2 (PREX2) is a novel regulator of the small guanosine triphosphatase Rac, and has been observed to be implicated in human cancer by inhibiting the activity of phosphatase and tensin homolog (PTEN), thus upregulating the activity of the phosphoinositide 3-kinase (PI3K) signaling pathway. However, the exact role of PREX2 in pancreatic cancer has not been reported to date. In the present study, the expression levels of PREX2 were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The gene overlap between HepG2 PPA and the Sanger Cancer Gene Census is 19 (Supplementary Table S6). HepG2 PPA variants include oncogenes and tumor suppressors such as NRAS (47), STK11/LKB1 (48) and PREX2 (49,50) as well as other genes recently found to play critical roles in driving cancer such as CDK12 (51) and IKBKB (52,53) . RP1L1 , which was recently found to be significantly mutated in hepatocellular carcinoma (45), is also present among the PPA variants.…”
Section: Resultsmentioning
confidence: 99%
“…The gene overlap between HepG2 PPA and the Sanger Cancer Gene Census is 19 (Supplementary Table S6). HepG2 PPA variants include oncogenes and tumor suppressors such as NRAS (47), STK11/LKB1 (48) and PREX2 (49,50) as well as other genes recently found to play critical roles in driving cancer such as CDK12 (51) and IKBKB (52,53) . RP1L1 , which was recently found to be significantly mutated in hepatocellular carcinoma (45), is also present among the PPA variants.…”
Section: Resultsmentioning
confidence: 99%
“…For example, we identified CN changes (CN=3) over the oncogene VEGFA (6p21.1) which is widely known as a key mediator of angiogenesis in cancer (Carmeliet 2005). We see mutations in oncogenes and tumor-suppressor genes in HepG2, such as NRAS (Pylayeva-Gupta et al 2011), STK11/LKB1 (Zhou et al 2014), and PREX2 (Berger et al 2012;Yang et al 2016), as well as in the Wnt-pathway gene CTNNB1 due to the presence of either HepG2-specific protein-altering changes or small-scale structural changes (Table S5, Table S6, Dataset 1, Dataset 4, Supplemental Data). Moreover, we also identified mutations in genes recently found to play critical roles in driving cancer such as CDK12 (Paculová and Kohoutek 2017) and IKBKB (Xia et al 2012;Kai et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The gene overlap between HepG2 PPA and the Sanger Cancer Gene Census is 19 (Table S6). HepG2 PPA variants include oncogenes and tumor suppressors such as NRAS (Pylayeva-Gupta et al 2011), STK11/LKB1 (Zhou et al 2014), and PREX2 (Berger et al 2012;Yang et al 2016) as well as other genes recently found to play critical roles in driving cancer such as CDK12 (Paculová and Kohoutek 2017) and IKBKB (Xia et al 2012;Kai et al 2014). RP1L1, which was recently found to be significantly mutated in hepatocellular carcinoma (Cancer Genome Atlas Research Network 2017) is also present among the PPA variants.…”
Section: Snvs and Indelsmentioning
confidence: 99%
“…As we all know, the adhesion function of cells is the primary step for tumor metastasis [46], and the adhesion function enhanced by the focal adhesion and ECM-receptor interaction can accelerate cancer cell metastasis in the blood vessels. The PI3K signaling pathway is activated in a variety of tumors including pancreatic cancer, and the activation of PI3K signaling pathway promotes the metastasis of tumor cells [47].…”
Section: Discussionmentioning
confidence: 99%